Analysis of E-Consumer Behaviour – Selected Findings from an Analysis of Czech E-Shops and their Customers during the Global Pandemic - Pollak Frantisek (SHS Web of Conferences, 2021)
The study presented in this contribution deals with the issue of using modern methods of data collection for the purposes of analysing consumer behaviour. Professional literature as well as business practice offer us an enormous number of approaches, traditional or innovative, with which it is possible to obtain and then evaluate data in order to understand specific patterns of consumer behaviour. Following on from our previous research in the field, we have applied a method of collecting and evaluating customers e-data in real time. As a source of data, we used the virtual social network Facebook. As a sample we selected customers of the five largest e-shops operated in the Czech Republic. On a sample of more than one and a half million users we monitored the B2C communication of e-shops and subsequently the C2B Facebook interaction of their customers during the lockdown caused by the COVID-19 pandemic. In the observed period we analysed hundreds of thousands of interactions and then outlined basic trends and specific characteristics of consumer behaviour suitable for further research. The selected findings resulting from the implemented analyses contribute to the creation of a knowledge base of a qualitative nature, which can help to define research goals in the future process of examining the effects of the pandemic on various aspects of business.